Assessment of RCPCH interview process for ST1 run through posts in our deanery. (24th May 2012) - Bond, E; Fine-Goulden, M; Karim, S; Minson, S; Taylor, F; Katugampola, H; Broughton, S
Abstract : Aims: In January 2010, candidates applying for Paediatric Speciality Training completed a nationalised electronic application. Successful candidates were invited to a standardised interview, comprising of an oral presentation, structured interview and communication scenario. We aimed to assess which stations were most helpful in assessing candidate appointability, as well as candidates' experience of the interview process. Methods: Following interview, candidates were invited to complete a feedback questionnaire online, using a password-protected survey site. Anonymised interview scores were obtained from the RCPCH and binary logistic regression used to assess the impact of each individual stations combined scores on whether a candidate was appointable. Results: 41% (90/218) of ST1 candidates interviewed responded to the questionnaire. Most felt that PowerPoint, rather than acetates for a projector, would provide a more reliable measure of presentation skills, as candidates are more familiar with this in their everyday practice. Candidates expressed concern about lack of sustained interest of interviewers during the presentation. Many candidates felt that insufficient time allowed for the interview and portfolio stations meant they were unable to express personal strengths and achievements. There was no significant concern about the communication station. Binary logistic regression analysis of the scores of each individual station, demonstrated that the communication (p<0.001) and portfolio stations (p<0.001) were significantly associated with being considered appointable. Neither the interview (p=0.289) or presentation stations (p=0.055) were associated. Conclusion: We believe this to be the most extensive review of the Speciality Training interview process in Paediatrics in the UK. The communication and portfolio stations were most discriminating when assessing appointability to an ST1 post. Candidates expressed concern with regard to the presentation and interview stations and we did not find these to be associated with whether a candidate was considered appointable. Alterations have since been made to the format of the RCPCH interview process. We hope these changes continue to ensure the selection of the highest calibre candidates to paediatric ST1 posts and a positive interview experience encourages them to take up the posts offered.